"Yubi‐wakka" (finger‐ring) test: A practical self‐screening method for sarcopenia, and a predictor of disability and mortality among Japanese community‐dwelling older adults. Issue 2 (12th September 2017) - Tanaka, Tomoki; Takahashi, Kyo; Akishita, Masahiro; Tsuji, Tetsuo; Iijima, Katsuya
Abstract: Aim: We developed a simple self‐screening method, the "Yubi‐wakka (finger‐ring)" test to assess sarcopenia swiftly. This prospective cohort study aimed to examine the validity of this test as a practical method among community‐dwelling older adults for identifying sarcopenia, and for predicting disability and mortality. Methods: We followed 1904 older adults, and analyzed associations between this "Yubi‐wakka" test result at baseline in 2012 and sarcopenia at baseline, new‐onset sarcopenia followed until 2014, and new‐certification for the long‐term care insurance and mortality followed until 2016. The "Yubi‐wakka" test checks whether the maximum non‐dominant calf circumference is bigger than the individual's own finger‐ring circumference, which is formed by the thumb and forefinger of both hands. We divided participants into three groups, "bigger, " "just fits" and "smaller" based on a comparison between the calf and finger‐ring circumference. Results: Of 1904 participants (mean age 72.8 ± 5.4 years), 53% were grouped as "bigger, " 33% were in "just fits" and 14% were in "smaller." Relative to "bigger, " the test results statistically associated with sarcopenia ("just fits" OR 2.4, 95% CI 1.4–4.1 and "smaller" OR 6.6, 95% CI 3.5–13), by multivariate analyses. The test results also increased the risk of new‐onset sarcopenia ("just fits" HR 2.1, 95% CI 1.2–3.8 and "smaller" HR 3.4, 95% CI 1.8–6.4). Furthermore, the "smaller" had 2.0‐ and 3.2‐fold increased risks for needing long‐term care insurance services and mortality, respectively. Conclusions: The "Yubi‐wakka" test is an extremely practical method to identify older adults at risk of sarcopenia, disability and mortality. This test might contribute to increased primary prevention for sarcopenia by serving as an early wake‐up call for older adults against becoming sarcopenic.Geriatr Gerontol Int 2018; 18: 224–232 .